TYPOLOGY OF MUHAMMAD NASHIRUDDIN AL-ALBANI'S HADITH THOUGHT - Syahidin, Syahidin (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
This article discusses the typology of the thought of Muhammad Nashiruddin al-Albani, a prominent hadith scholar in the modern era who is widely known among Salafi manhaj. As a scholar who emphasizes the importance of tashfiyah (purification) in hadith, Al-Albani seeks to distinguish authentic hadith from dha'if hadith, which he believes is a fundamental step to eliminate heresy and superstition in Islamic practice. Through a descriptive-analytical approach, this article shows that Al-Albani is not only a hadith scholar, but also a reformist who seeks to bring Muslims back to the pure teachings based on salaf al-shalih. Thus, his thinking has a great influence in shaping modern Islamic discourse, especially in the study of hadith and the implementation  of manhaj salaf. On the other hand, his views also raised polemics among other scholars, especially related to his rejection of the taqlid madhhab. Al-Albani is not only known as a hadith scholar, but also as a reformer who revived the spirit of Islam based on authentic principles. His thinking provides a strong intellectual foundation for those who want to understand and practice Islamic teachings according to the guidance of the salaf generation.